The empire of economics (1997)
This article comments on the use of microeconomic instruments in fields that once were the exclusive preserve of the other social sciences, and its consequences for current theoretical activities. It looks particularly at the Theory of the Family by Becker, who has been accused of being the person most responsible for 'economic imperialism', that is, for applying the view of the calculating and selfish individual --homo economicus-- to the study of social processes that had usually been explained by means of history or institutions. In spite of strong criticisms of Becker, the author considers his work to be meritorious insofar as it contributes to showing, in a passive form, the excessive 'padding' that is hidden behind the trivialities or the darkness --which is not profundity but rather vacuity-- of certain social literature.